STUDY OF INFLUENCE ZINC LEVEL IN BLOOD IN PATIENTS WITH CHRONIC PYELONEPHRITIS ON THE ACTIVITY OF INFLAMMATORY PROCESSES IN KIDNEYS - I. S. Lisnyanska (Ukrainian Journal of Nephrology and Dialysis, 2017)
Materials and methods: examined 67 patients with chronic pyelonephritis. All patients were determined level of zinc in the blood and levels of inflammatory cytokines, C-reactive protein in the urine.Results. We found a significant decrease in the level of zinc in the blood of patients with chronic pyelonephritis (p<0.05). As for the performance of proinflammatory cytokines and CRP, we found a significant increase in IL-6 (p<0.001), TNF-α (p<0.001) and CRP (p<0.05) in the urine, indicating that the activity of the inflammatory response in situ. In applying the basic therapy levels of zinc in the blood were not significantly changed (p>0.05), and the application of basic therapy in combination with zinc sulfate significantly increased (p<0.05) and almost no difference in the values of group norms. Analyzing changes in cytokines and CRP in urine during treatment, we found a significant decrease in these indicators as the application of basic care and the application tested therapy, but the application of the second we found a greater decrease in these indicators, in some cases reaching values of group norms.Conclusions. The preparation of zinc may be a promising direction of the treatment of chronic pyelonephritis, since increases this microelement in the blood and reduces the activity of inflammatory response in the kidney.